FAKTOR YANG BERHUBUNGAN DENGAN KINERJA KADER POSYANDU DI WILAYAH KERJA PUSKESMAS X - Raviola Raviola; Muhammad Dedi Widodo (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The integrated service cadre performance is the result of work, both the quality and quantity achieved by human resources unity of time period in carrying out their duties in accordance with the responsibilities given to the cadres. Based on the background described above, the D / S coverage at the X public health center is 67.2% of the 80% target so that the D / S coverage at the X community health center has not yet reached the target, so the problem formulation that forms the basis of this research is to find out the factors related to the performance of integrated service post cadres in achieving D / S at the X public health center. This study aims to determine the factors associated with the performance of integrated service post cadres in achieving D / S at the X City Pekanbaru public health center. This type of research is a quantitative study with a cross sectional research design The sample consisted of 66 integrated service post cadres with sampling techniques using purposive sampling. The analysis used was univariate and bivariate analysis with Chi-square test, the measuring instruments used were questionnaires and computerized data processing. The results of the study showed that three variables had a relationship and one variable had no relationship. Knowledge (p value 0,068 POR value = 2,889), education (p value 0,089 POR value = 2,778), the role of health workers (p value 0,026 POR value 4,140) and support from community leaders (p value 0,270 POR value = 0.506). It is expected that health workers can maintain and improve the quality of services at integrated service posts in order to achieve programs in integrated service posts.